PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Sabar L.T Simatupang; Rudy Irsian; Mutia Miranda Nasution; Flestea Gaho (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
This study aims at determining the effect of Motivation and Work Discipline variables on Employee Work Productivity at PT. Perkebunan Nusantara III (Persero) Medan. The hypothesis used in this study is that there is the influence of Motivation and Work Discipline on Employee Work Productivity on PTPN III (Persero) Medan. The population at PTPN III (Medan) is 400 people, with a total sample of 80 people. The regression equation obtained is Y = 2.517 + 0.073X1 + 0.363X2. Based on the test results R Square results of 0.471 was obtained which means that Motivation (X1) and Work Discipline (X2) have on the Employee Productivity variable of 47.1% . Based on the results of the t-test (partial) and F test (simultaneous) the results obtained Motivation variable (X1), t count 2.333> t table 1.991 with a significance level of 0.035 < 0.05. Motivation has a positive effect on employee work productivity. Working Discipline Variable (X2), t arithmetic = 2.216> t table = 1.991 with a significance level of 0.028 < 0.05. Work discipline has a positive effect on employee work productivity. Variable Motivation (X1) and Work Discipline (X2), F count 4.007> F table 3.110 with a significance level of 0.022 < 0.05. It can be summarized that Motivation and Work Discipline together have positive effect on employee work productivity.